2016
DOI: 10.1038/srep37227
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Oncogenic transformation of human lung bronchial epithelial cells induced by arsenic involves ROS-dependent activation of STAT3-miR-21-PDCD4 mechanism

Abstract: Arsenic is a well-documented human carcinogen. The present study explored the role of the onco-miR, miR-21 and its target protein, programmed cell death 4 (PDCD4) in arsenic induced malignant cell transformation and tumorigenesis. Our results showed that treatment of human bronchial epithelial (BEAS-2B) cells with arsenic induces ROS through p47phox, one of the NOX subunits that is the key source of arsenic-induced ROS. Arsenic exposure induced an upregulation of miR-21 expression associated with inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…In addition to HIF-1α pathways, miRs also act as critical mediators of hypoxia signaling through other signaling pathways. Previous studies confirmed that activation of STAT3 regulates miR-21 expression, as there is a conserved STAT3-binding site locted in miR-21 genomic region 32 . Inhibition of the activation of STAT3 with the STAT3 inhibitor S3I-201 reduced the miR-21 expression, suggesting that p-STAT3 might work together with HIF-1α to induce the expression of miR-21 under hypoxia.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to HIF-1α pathways, miRs also act as critical mediators of hypoxia signaling through other signaling pathways. Previous studies confirmed that activation of STAT3 regulates miR-21 expression, as there is a conserved STAT3-binding site locted in miR-21 genomic region 32 . Inhibition of the activation of STAT3 with the STAT3 inhibitor S3I-201 reduced the miR-21 expression, suggesting that p-STAT3 might work together with HIF-1α to induce the expression of miR-21 under hypoxia.…”
Section: Discussionmentioning
confidence: 57%
“…Experiment was performed in triplicate and representative results are shown here. *P < 0.05 and #P < 0.01, compared with control and 0.5 μM) for 6 months (Pratheeshkumar et al, 2016) and 0.25 μM arsenite for 16 weeks (Zhang et al, 2012). Another study showed that human bronchial epithelial cells were malignantly transformed after exposure to 1.0 μM arsenite for about 15 weeks .…”
Section: Discussionmentioning
confidence: 96%
“…Consistently, Zhang et al () found that 0.25 μ m arsenite induced BEAS‐2B cell transformation after 24 weeks of exposure. BEAS‐2B cells could also be malignantly transformed after chronic exposure to low concentrations of arsenite (0.1, 0.25 and 0.5 μ m ) for 6 months (Pratheeshkumar et al, ) and 0.25 μ m arsenite for 16 weeks (Zhang et al, ). Another study showed that human bronchial epithelial cells were malignantly transformed after exposure to 1.0 μ m arsenite for about 15 weeks (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms have been described for arsenic mode of action. Many studies have reported increased generation of reactive oxygen and nitrogen species (ROS/RNS) as a result of cellular arsenic metabolism and induction of NADPH oxidase activity (16)(17)(18)(19). It has also been reported that arsenic-induced ROS deplete glutathione pools, cause oxidative modifications to lipids and proteins, affect mitochondrial integrity and function, and result in mutations or chromosomal aberrations, which may be exacerbated by the arsenic-mediated inhibition of DNA repair enzymes (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Metabolic conversion of arsenic to methylated forms consumes S-adenosylmethionine (SAM), a methyl group donor necessary for DNA and histone methylation (25). Moreover, recent studies have correlated arsenic exposure to alterations in microRNA (miRNA) expression (17,26).…”
mentioning
confidence: 99%